Construction and Potentiometric Study of Chloramphenicol Selective Electrodes Based on a PVC Matrix Membrane - Muhamad, Yasmeen H (Al-Nahrain Journal of Science, 2015)
Chloramphenicol succinate selective electrodes were prepared based on a complex Chloramphenicol succinate -phosphomolybdate as an active material using the plasticizers di-octyl phthalate (DOPH), tri-butyl phosphate (TBP), o-nitro phenyl octyl ether (ONPOE) and di-butyl phthalate (DBPH) in a PVC matrix membrane. The properties of the prepared electrodes were studied, such as: slope, concentration range, detection limit, lifetime, pH effect and selectivity. The experimental results showed that the best electrode was based on DOPH and DBPH as plasticizers, displaying a linear range from 1.00x10−4 M to 1.00x10−1 M and 1.00x10−1 M to 2.00x10−4 with a Nernstian slope of 58.5 mV/decade and 53.9 mV/decade, correlation coefficient of 0.9999 and 0.9998, The detection limit was 5.5x10−5 M and 8.0x10−5, the lifetime was around 40 and 25 days respectively. The proposed electrodes were successfully applied to the determination of in Chloramphenicol succinate a pharmaceutical preparation.